Fandom, unicórnios e modos de subjetivação LGBTQIAPN+: um estudo sobre os Earpers - Santos, Ingrid Xavier Gomes dos (2024)
This paper aims to investigate the fandom of the TV series Wynonna Earp (2016-2021), also known as Earpers, in the construction of the LGBTQIAPN+ subjectivity of its participants. This group is notable for its size and impact on an audiovisual product that is not economically robust. Based on Henry Jenkins' formulations about the idea of fandom, an active fan community that functions as spaces for exchange and interaction, we argue that these interactions operate as modes of subjectivation which, according to Foucault, deals with the particular way in which individuals become subjects, how they construct their subjectivities, develop an understanding of themselves and position themselves within a social structure. The research was also guided by Félix Guattari's concepts of subjectivity. We worked with data from an opinion poll in accordance with Resolution 510/2016 of the Research Ethics Committees (CEP/CONEP), using an online form answered by 100 participants. We found in the responses to this form aspects that link the experiences of fandom and the self-writing of its participants. We wanted to examine how interaction between fans, content production and appropriation practices forge the subjectivity of LGBTQIAPN+ participants in a fandom. In the end, we understood that a fandom can be a mode of subjectivation for its participants and we observed that it is possible for LGBTQIAPN+ people to find welcome and acceptance in a group of fans and that, in the case of the Earpers, this environment has allowed some individuals to construct new ideas of themselves and foster a community that is more open to differences.